Smart power : climate change, the smart grid, and the future of electric utilities - Fox-Penner, Peter S., 1955- (Island Press, 2014)
Few industries in the U.S. are as stuck in the past as our utilities are. In the face of growing challenges from climate change and the need for energy security, a system and a business model that each took more than a century to evolve must now be extensively retooled in the span of a few decades. Despite the need, many of the technologies and institutions needed are still being designed or tested. It is like rebuilding our entire airplane fleet, along with our runways and air traffic control system, while the planes are all up in the air filled with passengers. In this accessible and insightful book, Peter Fox-Penner considers how utilities interact with customers and how the Smart Grid could revolutionize their relationship. Turning to the supply side, he considers the costs of, and tradeoffs between, large-scale power sources such as coal plants and small-scale power sources close to customers. Finally, he looks at how utilities can respond to all of these challenges and remain viable, while financing hundreds of billions of dollars of investment without much of an increase in sales. Upon publication, Smart Power was praised as an instant classic on the future of energy utilities. This Anniversary Edition includes up-to-date assessments of the industry by such leading energy experts as Daniel Estes and Jim Rogers, as well as a new afterword from the author. Anyone who is interested in our energy future will appreciate the clear explanations and the in-depth analysis it offers.